Proposed framework for forecasting heat-effects on motor-cognitive performance in the Summer Olympics - Piil, J. F.; Kingma, B.; Morris, N. B.; Christiansen, L.; Ioannou, L. G.; Flouris, A. D.; Nybo, L. (Temperature, 2021)
Heat strain impairs performance across a broad spectrum of sport disciplines. The impeding effects of hyperthermia and dehydration are often ascribed to compromised cardiovascular and muscular functioning, but expert performance also depends on appropriately tuned sensory, motor and cognitive processes. Considering that hyperthermia has implications for central nervous system (CNS) function and fatigue, it is highly relevant to analyze how heat stress forecasted for the upcoming Olympics may influence athletes. This paper proposes and demonstrates the use of a framework combining expected weather conditions with a heat strain and motor-cognitive model to analyze the impact of heat and associated factors on discipline- and scenario-specific performances during the Tokyo 2021 games. We pinpoint that hyperthermia-induced central fatigue may affect prolonged performances and analyze how hyperthermia may impair complex motor-cognitive performance, especially when accompanied by either moderate dehydration or exposure to severe solar radiation. Interestingly, several short explosive performances may benefit from faster cross-bridge contraction velocities at higher muscle temperatures in sport disciplines with little or no negative heat-effect on CNS fatigue or motor-cognitive performance. In the analyses of scenarios and Olympic sport disciplines, we consider thermal impacts on "motor-cognitive factors" such as decision-making, maximal and fine motor-activation as well as the influence on central fatigue and pacing. From this platform, we also provide perspectives on how athletes and coaches can identify risks for their event and potentially mitigate negative motor-cognitive effects for and optimize performance in the environmental settings projected.